PERAN ORANG TUA DALAM MEMBENTUK KARAKTER ISLAMI PADA ANAK (STUDI KASUS DI LINGKUNGAN ZAENAL ZAKSE 1, KECAMATAN KEDUNGKANDANG, KELURAHAN KOTALAMA, KOTA MALANG) - Nurul Izza; Abd Jalil; Atikah Zuhrotus Sufiayana (VICRATINA, 2022)
This study discusses the role of parents in shaping the Islamic character of childrenin the Zaenal Zakse 1 environment, Kedungkandang District, Kotalama Village,Malang City. This research is motivated by this increasingly advanced era, manysay that the biggest problem faced by the Indonesian people is the moral aspect. InZaenal Zakse I's environment, there are many children who still yell at theirparents, are less enthusiastic in participating in Islamic activities, or lack etiquettefor the people around them in walking, talking, and socializing. Therefore, thisstudy aims to raise awareness for parents of the importance of the role of parentsin character education. The method used in this research is a qualitative methodwith a case study type approach. The data were obtained from various informantsof the parents of students in the Zaenal Zakse I environment. The data collectiontechniques used were interviews, observation and documentation. The results ofthis study, that parents in the Zaenal Zakse I environment, already have anawareness of their role. And considers that parents are the most important forchildren's morals. And have realized that morality is the most important numberone in life.